2012
DOI: 10.1155/2012/167096
|View full text |Cite
|
Sign up to set email alerts
|

Fc-Gamma Receptor 3B Copy Number Variation Is Not a Risk Factor for Behçet’s Disease

Abstract: Behçet's disease (BD) is an immune-mediated systemic vasculitis associated with HLAB51. Other gene associations are likely and may provide further insight into the pathogenesis of this disease. Fc-gamma receptors play an important role in regulating immune function. Copy number variation (CNV) of the Fc-gamma receptor 3B (FCGR3B) gene is associated with other inflammatory conditions and may also play a role in BD. The aim of this study was to determine whether CNV of the FCGR3B gene is associated with BD or it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Associations have been reported with both low [9] and high [8] copy number, whilst other studies have not identified such an association (reviewed in [16]). We have also previously reported that FCGR3B CNV is not a risk factor for Behcet's disease [17] in Iranian patients. The aim of this study was to evaluate the association between FCGR3B CNV and biopsy-proven GCA in an Australian patient cohort.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Associations have been reported with both low [9] and high [8] copy number, whilst other studies have not identified such an association (reviewed in [16]). We have also previously reported that FCGR3B CNV is not a risk factor for Behcet's disease [17] in Iranian patients. The aim of this study was to evaluate the association between FCGR3B CNV and biopsy-proven GCA in an Australian patient cohort.…”
Section: Introductionmentioning
confidence: 76%
“…Both low and high FCGR3B copy number (<2) have been associated with anti-neutrophil cytoplasmic antibody-associated systemic vasculitides [8, 9], with a third study [18] observing no association. Other studies have reported no FCGR3B CNV associations with Kawasaki disease [19], antiglomerular basement membrane disease [20], and Behcet's disease [17] nor with vasculitis complicating systemic lupus erythematosus [21]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the high prevalence of BD in Iran and the severe influences that disease may induce on daily activity, assessment of quality of life in this cohort was essential. This becomes particularly more important since diseasespecific quality-of-life measure may evaluate the impact of disease on areas that are not adequately addressed in routine clinical practice or in generic questionnaire that may lack one or more domains pertinent to BD patients (e.g., problems with talking and eating for patients with mouth ulceration and effect on relationships) [8,25].…”
Section: Discussionmentioning
confidence: 99%
“…There were also some studies targeting the relationship between FCGR3B CNVs and BD. Black et al (2012 ) found that CNV of the FCGR3B gene was associated with the risk of BD in the Iranian population. The risk of BD was decreased by 40% in people with less than two copies of FCGR3B and by 25% in people with more than two copies of FCGR3B , although these tendencies were not statistically significant.…”
Section: Behcet’s Diseasementioning
confidence: 99%